Implementation of the Obligations and Responsibilities of Notaries in Providing Social Services According to Their Position in the City of Cirebon - Kamaluddin, Muhammad Risyad; Taufiq, Muhammad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract.This study aims to determine and analyze the Implementation of Notary Obligations and Responsibilities in Providing Social Services According to Their Position in the City of Cirebon and analyze what obstacles are encountered when implementing Notary Obligations and Responsibilities in Providing Social Services. This type of research is an empirical legal research. The approach method in this study is a Qualitative Approach. The types and sources of data in this study are primary and secondary data obtained through interviews and literature studies. The analysis in this study is Descriptive Analytical. Based on the results of the study, it was concluded that the legal regulations regarding notary obligations in providing social services to the poor are contained in Article 37 paragraph (1) UUJN and Article 3 paragraph (7) of the Notary Code of Ethics. In practice, Notary Lia Amalia, SH, has carried out her obligations in accordance with the provisions of the Notary Law, legal services are not only provided to poor clients but also provided for foundation activities, activities in the social, humanitarian and religious fields. Notaries assess the poor based on humanity and conscience. Meanwhile, the obstacles encountered are that the provisions in Article 37 paragraph (1) of the UUJN do not explain in detail the procedures and who is said to be able to receive legal assistance to determine whether someone is eligible or can be exempted from fees, and there is still a lot of stigma in society regarding the services of a Notary as being very expensive. Keywords: Poor People; Notary; Responsibility; Social Services; Obligations.